THE EFFECTIVENESS OF ONLINE LEARNING IN THE NEW NORMAL ERA ON LEARNING MOTIVATION AND UNDERSTANDING LEVEL OF STUDENTS OF PGSD UNIVERSITY WIJAYA KUSUMA SURABAYA - Noviana Desiningrum; Endang Nuryasana (Jurnal Inovasi Penelitian, 2022)
The teaching and learning process is currently experiencing changes in the era of the Covid-19 pandemic that hit the world that no one could ever imagine. This makes all countries, including Indonesia, inevitably have to be able to adapt to these new conditions as a form of new normal (new normal) to carry out daily activities. Schools are required to be able to do learning using online/online applications as well as universities. So, the purpose of this research is to find out how effective online learning that has been taught is on students' motivation and level of understanding. The research subjects were PGSD students at Wijaya Kusuma University Surabaya who actively participated in lectures for even semester students of the 2020/2021 academic year, namely in semester 4 and semester 6 students, totaling 20 people. The research method uses a qualitative descriptive method, with data collection using online interviews and online questionnaires. The results obtained include: student activities in learning get a score of 3 which means quite good, student responses to learning are 73%, student learning outcomes in semester 4 are 76.31%, and semester 6 are 79%. The output of this research is an accredited national journal